Sisa's vengeance Jose Rizal's sexual politics & cultural revolution - San Juan, E., Jr. 1938- (Vibal Foundation, Inc., 2021)
In Sisa’s Vengeance: Jose Rizal’s Sexual Politics and Cultural Revolution, acclaimed literary scholar E. San Juan Jr. casts a critical eye on the biases of some of the prominent scholarship of Rizal over the decades. This book invites readers to look past the popular image of Rizal in order to understand his ideas as embodied in his work, and how these ideas and beliefs were shaped by the events and circumstances of his life. In the essays gathered here, the author uses the perspective of historical materialism to consider Rizal as a social and historical product of the time he lived in. San Juan argues that Rizal’s criticism of colonial society can be gleaned from the tribulations facing his fictional women characters like Sisa, and that these injustices reflected the circumstances of the various women in his own life. Thus Rizal recognized gender equality as a key component of national liberation.